Kajian Ekologi Sastra dalam Cerita Rakyat Provinsi Daerah Istimewa Yogyakarta - Muhammad Alfian Hermawan; Yosi Wulandari (Universitas Negeri Padang, 2021)
Folklore is about moral values, cultural values, psychological values, and advice in living a life. In the legend of Yogyakarta Special Region Province and containing moral values, there are also ethics in treating the universe. It is proven by the folklore of Yogyakarta Special Region Province there are concepts of environmental ethics in it. Such as respect for nature, responsibility to heart, cosmic solidarity, compassion and care for the character, no harm and simple living, and harmony with nature. The physical background in Yogyakarta Special Region Province's folklore also uses many physical locations in the form of environment, such as forests, rivers, hills, villages, fields. Literary ecology has a part in this because literary ecology is a science that discusses the reciprocal relationship between literature and nature, or vice versa. Keywords: Folklore, Literary Ecology, Environmental Ethics, Physical Background (Environment)